2017
DOI: 10.1016/j.phrs.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

A signalome screening approach in the autoinflammatory disease TNF receptor associated periodic syndrome (TRAPS) highlights the anti-inflammatory properties of drugs for repurposing

Abstract: 2Abbreviations: BCA, bicinchoninic acid; CV, coefficient of variation; MTT, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide; PBMCs, peripheral blood mononuclear cells; RPPA, reverse phase protein array; SSMD, strictly standardised mean difference; TNFR1, tumour necrosis factor receptor-1; TRAPS, TNF receptor associated periodic syndrome; WT, wild type. 3ABSTRACT: TNF Receptor Associated Periodic Syndrome (TRAPS) is an autoinflammatory disease caused by mutations in TNF Receptor 1 (TNFR1). Current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Grassi et al found that antibiotic lomefloxacin can treat acute exacerbations of chronic bronchitis [62]. Using the signalome screening method, Todd et al reported that lomefloxacin showed significant effects on multiple pro-inflammatory signaling pathways that are constitutively activated in the auto-inflammatory disease TNF receptor [63]. However, no study has been performed concerning the usage of lomefloxacin for asthma treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Grassi et al found that antibiotic lomefloxacin can treat acute exacerbations of chronic bronchitis [62]. Using the signalome screening method, Todd et al reported that lomefloxacin showed significant effects on multiple pro-inflammatory signaling pathways that are constitutively activated in the auto-inflammatory disease TNF receptor [63]. However, no study has been performed concerning the usage of lomefloxacin for asthma treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Using cell line models depicting TRAPS, as well as PBMC lysates from C33Y-TRAPS patients relative to controls, the RPPA approach was combined with the screening of existing pharmacologically active compounds to identify key compounds which modulate the TRAPS signalome. The fluoroquinolone antibiotic, lomefloxacin, as well as others from the same class of compounds was found to have the most significant effects on pro-inflammatory pathways in TRAPS (116). This approach would be useful for other autoinflammatory diseases to identify cellular pathways in the disease state as well as candidates for drug repurposing.…”
Section: Tnf Therapeutic Alternativesmentioning
confidence: 98%
“…An interesting investigative approach has been developed for TRAPS, whereby new technologies, -'PPA), can be used to detect and quantify intracellular signalling molecules associated with a particular disease phenotype (116). Using cell line models depicting TRAPS, as well as PBMC lysates from C33Y-TRAPS patients relative to controls, the RPPA approach was combined with the screening of existing pharmacologically active compounds to identify key compounds which modulate the TRAPS signalome.…”
Section: Tnf Therapeutic Alternativesmentioning
confidence: 99%
“…The study of signaling pathways and its regulation (signaloma) through the application of reverse-phase protein microarray (RPPA) technology has been recently adopted for TRAPS [ 72 ]. So far, the focus of the treatment of these patients has been the blockage of proinflammatory cytokines instead of targeting intracellular proinflammatory signaling pathways.…”
Section: Inflammasomopathies/monogenic Recurrent Feversmentioning
confidence: 99%
“…The most ranked drug was the antibiotic lomefloxacin that significantly reduced the expression of several molecules across the Jak/Stat, MAPK, NF-kB and PI3K/AKT pathways. Although at a preliminary stage, this would be matter of future research for TRAPS and other AIDs [ 72 ].…”
Section: Inflammasomopathies/monogenic Recurrent Feversmentioning
confidence: 99%